AN OVERVIEW OF THE CHARACTERISTICS OF NUTRITIONAL STATUS WITH ISPA SUFFERERSIN TODDLERS AT THE BONE ROMBO HEALTH CENTER, NORTH BUTON DISTRICT IN 2023 - Nurwiwin, Nurwiwin; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
Acute respiratory infection is a health problem in Indonesia, mainly because acute respiratory infection causes many deaths and morbidity. Respiratory tract infections are a problem of death and morbidity for toddlers and children in Indonesia. Acute Respiratory Infection is a case of infectious disease that often occurs in toddlers where one of the risks of ARI is caused by individual factors in the child, such as the density of the house's occupants, home ventilation, regularity of giving vitamins, and air pollution. This study aims to determine the characteristics of sufferers' status. Nutrition with the Incidence of Acute Respiratory Infection in Toddlers at Bone Rombo Community Health Center, North Buton Regency in 2023. The type of research used is quantitative descriptive research which describes in general the characteristics of patients with Respiratory Tract Infection in the working area of the Bone Rombo Health Center, North Buton using research subjects as toddler patients who diagnosed with acute respiratory infection. Obtained from the results of medical records there is a relationship between nutritional status and the incidence of respiratory infections in toddlers and the results obtained from 0-36 months are very susceptible to acute respiratory infections. Conclusion Based on the results of medical record data there were 142 toddler patients with Respiratory Tract Infection where there were 78 male patients 55%, there were in the age group the most were toddlers aged 0-36 namely 105 people 74% and patients and where based nutritional status, namely the highest in the category of undernutrition as many as 99 people 70% Keywords: Respiratory Tract Infectious; Nutritional Status